The cancer nursing workforce in Australia: a national survey exploring determinants of job satisfaction - Natalie Bradford; Elizabeth Moore; Karen Taylor; Olivia Cook; Lucy Gent; Theresa Beane; Natalie Williams; Kimberly Alexander; Erin Pitt; Jemma Still; Cameron Wellard; Gemma McErlean; et al. (BMC, 2023)
Abstract Background To maintain and improve the quality of the cancer nursing workforce, it is crucial to understand the factors that influence retention and job satisfaction. We aimed to investigate the characteristics of cancer nurses in Australia and identify predictors of job satisfaction. Methods We analysed data from an anonymous cross-sectional survey distributed through the Cancer Nurses Society Australia membership and social media platforms from October 2021 to February 2022. The survey was compared to national nursing registration data. Data were analysed with non-parametric tests, and a stepwise, linear regression model was developed to best predict job satisfaction. Results Responses were received from 930 cancer nurses. Most respondents (85%) described themselves as experienced nurses, and more than half had post-graduate qualifications. We identified individual, organizational, and systemic factors that contribute to job satisfaction and can impact in workforce shortages. The findings include strategies to address and prioritize workforce challenges. There were 89 different titles for advanced practice nursing roles. Managing high workload was a reported challenge by 88%. Intention to stay less than 10 years was reported by nearly 60%; this was significantly correlated with job satisfaction and age. Significantly higher scores for job satisfaction were associated with those who had career progression opportunities, career development opportunities, adequate peer support and a clearly defined scope of role. Conversely, job satisfaction scores decreased the more people agreed there was a lack of leadership and they had insufficient resources to provide quality care. Conclusion Cancer nurses are critical to the delivery of cancer care however, the workforce faces multiple challenges. This study provides an understanding of the Australian cancer nursing workforce characteristics, their roles and activities, and highlights important considerations for retaining nurses in the profession.